The Technical and Business Analysis of Using Shore Power Connection in The Port of Hamburg - Devi Hotnauli Samosir; M Markert; Wolfgang Busse (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2016)
In port, when the ship is berthing the loading, unloading, and hospitality activity is using auxiliary engine. The combustion of marine fuels is a major contributor to air pollution, the air pollution is released 400 km around the port area. The impacts of the pollution are respiratory, health, and the environment around ports. Study indicates 60.000 of cardiopulmonary mortalities caused by ship air emission. Ship emission represents 3% of global CO2, 15% of global NOx, and 6% of global SOx emission. Because of that Hamburg Port is released the shore power facilities in July 2015 with idea of smart port and use the renewable energy such as wind turbine and solar panel compliance with IEC-ISO-IEEE 8005-1. In this bachelor thesis, the cost and also the condition between shore power and auxiliary engine will be analyzed and compared to find the most economical between shore power facilities and ship’s auxiliary engine. Shore power facilities in Hamburg are provided by SIEMENS with SIHARBOR and use a robot arm by Stemman Technik as the cable management system. The goal of this thesis is developed calculation tool to see the cost comparison and also the emission. And from the calculation tool the shore power is reducing the emission by 100% because of using the renewable energy and become economical than using auxiliary engine, it can save up to €1000. The other benefits are ship owner can save maintenance of their auxiliary engine and also saved the file. It shows that the shore power is a proven technology to reduce the emission and saved berth cost.